# How to Solve Equations for the Indicated Variable

••• BananaStock/BananaStock/Getty Images
Print

Elementary algebra is one of the main branches of mathematics. Algebra introduces the concept of using variables to represent numbers and defines the rules on how to manipulate equations containing these variables. Variables are important because they allow for the formulation of generalized mathematical laws and allow the introduction of unknown numbers into equations. It is these unknown numbers that are the focus of algebra problems, which usually prompt you to solve for the indicated variable. The "standard" variables in algebra are frequently represented as x and y.

1. ## Isolate the Variable

2. Move any constant values from the side of the equation with the variable to the other side of the equals sign. For example, for the equation 4x² + 9 = 16, subtract 9 from both sides of the equation to remove the 9 from the variable side: 4x² + 9 - 9 = 16 - 9, which simplifies to 4x² = 7.

3. ## Divide by the Coefficient (If Present)

4. Divide the equation by the coefficient of the variable term. For example, if 4x² = 7, then 4x² ÷ 4 = 7 ÷ 4, which results in x² = 1.75.

5. ## Take the Root of the Equation

6. Take the proper root of the equation to remove the exponent of the variable. For example, if x² = 1.75, then √x² = √1.75, which results in x = 1.32.

1. ## Isolate the Variable Expression

2. Isolate the expression containing the variable by using the appropriate arithmetic method to cancel out the constant on the side of the variable. For example, if √(x + 27) + 11 = 15, you would isolate the variable using subtraction: √(x + 27) + 11 - 11 = 15 - 11 = 4.

3. ## Apply an Exponent to Both Sides of the Equation

4. Raise both sides of the equation to the power of the root of the variable to rid the variable of the root. For example, √(x + 27) = 4, then √(x + 27)² = 4² which gives you x + 27 = 16.

5. ## Cancel the Constant

6. Isolate the variable by using the appropriate arithmetic method to cancel out the constant on the side of the variable. For example, if x + 27 = 16, by using subtraction: x = 16 - 27 = -11.

1. ## Set the Quadratic Equation Equal to Zero

2. Set the equation equal to zero. For example, for the equation 2x² - x = 1, subtract 1 from both sides to set the equation to zero: 2x² - x - 1 = 0.

3. ## Factor or Complete the Square

4. Factor or complete the square of the quadratic, whichever is easier. For example, for the equation 2x² - x - 1 = 0, it is easiest to factor so: 2x² - x - 1 = 0 becomes (2x + 1)(x - 1) = 0.

5. ## Solve for the Variable

6. Solve the equation for the variable. For example, if (2x + 1)(x - 1) = 0, then the equation equals zero when: 2x + 1 = 0 becomes 2x = -1 becomes x = -(1/2) or when x - 1 = 0 becomes x = 1. These are the solutions to the quadratic equation.

1. ## Factor the Denominators

2. Factor each denominator. For example, 1/(x - 3) + 1/(x + 3) = 10/(x² - 9) can be factored to become: 1/(x - 3) + 1/(x + 3) = 10/(x - 3)(x + 3).

3. ## Multiply by Least Common Multiple of Denominators

4. Multiply each side of the equation by the least common multiple of the denominators. The least common multiple is the expression that each denominator can divide evenly into. For the equation 1/(x - 3) + 1/(x + 3) = 10/(x - 3)(x + 3), the least common multiple is (x - 3)(x + 3). So, (x - 3)(x + 3) (1/(x - 3) + 1/(x + 3)) = (x - 3)(x + 3)(10/(x - 3)(x + 3)) becomes (x - 3)(x + 3)/(x - 3) + (x - 3)(x + 3)/(x + 3 = (x - 3)(x + 3)(10/(x - 3)(x + 3).

5. ## Cancel and Solve for the Variable

6. Cancel terms and solve for x. For example, cancelling terms for the equation (x - 3)(x + 3)/(x - 3) + (x - 3)(x + 3)/(x + 3) = (x - 3)(x + 3)(10/(x - 3)(x + 3) finds: (x + 3) + (x - 3) = 10 becomes 2x = 10 becomes x = 5.

1. ## Isolate the Exponential Expression

2. Isolate the exponential expression by cancelling any constant terms. For example, 100(14²) + 6 = 10 becomes 100(14²) + 6 - 6 = 10 - 6 = 4.

3. ## Cancel the Coefficient

4. Cancel out the coefficient of the variable by dividing both sides by the coefficient. For example, 100(14²) = 4 becomes 100(14²)/100 = 4/100 = 14² = 0.04.

5. ## Use the Natural Logarithm

6. Take the natural log of the equation to bring down the exponent containing the variable. For example, 14² = 0.04 becomes: ln(14²)= ln(0.04) = 2 × ln(14) = ln(1) - ln(25) = 2 × ln(14) = 0 - ln(25).

7. ## Solve for the Variable

8. Solve the equation for the variable. For example, 2 × ln(14) = 0 - ln(25) becomes: x = -ln(25)/2ln(14) = -0.61.

1. ## Isolate the Logarithmic Expression

2. Isolate the natural log of the variable. For example, the equation 2ln(3x) = 4 becomes: ln(3x) = (4/2) = 2.

3. ## Apply an Exponent

4. Convert the log equation to an exponential equation by raising the log to an exponent of the appropriate base. For example, ln(3x) = (4/2) = 2 becomes: eln(3x) = e².

5. ## Solve for the Variable

6. Solve the equation for the variable. For example, eln(3x) = e² becomes 3x/3 = e²/3 becomes x = 2.46.